A saúde do homem: doenças crônicas não transmissíveis e vulnerabilidade social - Bertolini, Daniele Natália Pacharone [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This project uses a mixed sequential approach. A multi method is used to evaluate and predict health risks related to chronic non-communicable diseases in men, according to social vulnerability experienced by them in the place where they live. Three sequential methods were outlined aiming at: (1) evaluating the relationship between absenteeism to medical appointments and number of chronic non-communicable diseases; (2) checking the relationship between spatial distribution of men bearing chronic non-communicable diseases and social vulnerability; (3) comprehending the health assistance plans proposed by coordinators of Basic Health Care Units to the male population, and the knowledge they have regarding the National Policy of Integrated Health Care for men. The study was conducted in a city of São Paulo state. Methods one and two were quantitative and used secondary data of the Integrated Health Information System (SIMIS, in Portuguese language acronym) of fifteen Units of Primary Health Care. The third method was qualitative, and the Content Analysis was used based on interviews with coordinators of Basic Care Units. Results from the quantitative analyses showed that the higher the absenteeism, the lower the number of noncommunicable diseases and the International Classification of Diseases. Moreover, the older the person is, the higher the number of non-communicable diseases and the number of chronic non-communicable diseases. Also, an increase in International Classification of Diseases and number of chronic non-communicable diseases were observed among men with a stable partner. The International Classification of Diseases which had spatial dependence were the neoplasms (colon and prostate cancer) and symptoms, abnormal signs and findings of clinical and laboratory exams not else classified (impaired glucose tolerance) in the urban area. Regarding the results of qualitative methodology, four thematic categories were found as ...

Trata-se de projeto de pesquisa de abordagem mista sequencial, organizado em multimétodos para avaliar e predizer agravos de saúde em homens, relativos às doenças crônicas nãotransmissíveis (DCNT), segundo a vulnerabilidade social (VS) vividos no espaço onde os mesmos habitam. Foram delineados três métodos sequenciais, visando: (1) avaliar a relação entre o absenteísmo em consultas agendadas e o número de doenças crônicas nãotransmissíveis (DCNT); (2) averiguar a relação entre distribuição espacial de homens com DCNT e VS; (3) conhecer as propostas implementadas por coordenadores de unidades de Atenção Básica para o atendimento da população masculina e o conhecimento que dispõem sobre a Política Nacional de Atenção Integral à Saúde do Homem (PNAISH). Foi conduzida em município do interior paulista, sendo os métodos um e dois de cunho quantitativo, com dados secundários do Sistema de Informação SIMIS das 15 unidades de saúde selecionadas, que foram tratados estatisticamente. O terceiro objetivo constituiu-se de delineamento qualitativo, tendo como técnica de coleta de dados a entrevista semi-estruturada com coordenadores dessas unidades e a Análise de Conteúdo como referencial metodológico. Os resultados encontrados na parte quantitativa foram quanto maior o número de faltas, menor é o número de DCNT e menor a quantidade de Classificação Internacional de Doenças (CID), além disso, quanto maior a idade, maior a quantidade de CID e de DCNT e houve maior quantidade de CID e de DCNT entre os homens com companheira (relação estável). As CID que tiveram dependência espacial foram as de neoplasias (Câncer de cólon e de próstata) e sintomas, sinais e achados anormais de exames clínicos e de laboratório, não classificados em outra parte (intolerância à glicose), na zona urbana. Com relação aos resultados da metodologia qualitativa foram encontradas quatro categorias temáticas:...
Keywords: Homens - Saúde e higiene; Cuidados primários de saúde; Doenças cronicas; Bem-estar social; Men - Health and hygiene